THE INFLUENCE OF SECRETOME THERAPY ON ERECTILE DYSFUNCTION AND D-DIMER LEVELS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - DIGAMBIRO, REZA ADITYA (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2024)
Introduction: The study aimed to determine the therapeutic effect of adipose-derived mesenchymal stem cell (MSC)-derived secretome on erectile function and D-dimer level, a biomarker for vascular health in T2DM men.Methods: An RCT performed on men aged 40 to 70 years with both T2DM and ED. The subjects were randomly allocated to receive secretome or placebo. Erectile function was measured by the International Index of Erectile Function (IIEF) questionnaire. They also had D-dimer levels measured before and after the intervention (ie, at 12 weeks). The primary analysis investigated differences in change of IIEF scores and D-dimer levels between groups using statistical tests. Moreover, we calculated a Pearson correlation coefficient to examine the relationship of both outcomes.Results: IIEF scores in the treatment group rose a mean of 3.06 points, compared to only half that amount with an increase of 0.5 points observed for control groups (p This difference was significant according to t-test (t = 6.72, p = 1.92e-07). The treatment group also experienced a more substantial decrease in D-dimer levels (-0.32 µg/mL on average) compared with the control group (an average change of -0.09 ug/ml), with a t-test statistic being-6.41(p = 4.44e−07). A minimal and not statistically significant correlation was also observed between improvements in IIEF scores with changes D-dimer levels (correlation coefficient: -0.11, p = 0.69).Conclusion : secretome therapy has demonstrated a significant increase in erectile function and reduction of D-dimer levels among patients with type 2 diabetes mellitus.